Role of the FtsA C Terminus as a Switch for Polymerization and Membrane Association - Marcin Krupka (American Society for Microbiology, 2014)
ABSTRACT Together with ATP, the C-terminal region of the essential streptococcal FtsA protein acts as an intramolecular switch to promote its polymerization and attachment to the membrane. During septation, FtsA is known to anchor the constricting FtsZ ring and, subsequently, the divisome to the membrane. Truncation of the C terminus of the streptococcal FtsA (FtsAΔCt) facilitates a more rapid ATP-dependent polymerization in solution than is seen with the full-length protein (FtsA+). The FtsAΔCt polymers are more organized and compact than those formed in solution by FtsA+, resembling the shape of the membrane-associated FtsA+ polymers. We find that ATP, besides being needed for polymerization, is required for the attachment of FtsA+ to lipid monolayers and to vesicle membranes. We propose a model in which the binding of ATP activates a switch favoring the polymerization of FtsA and at the same time driving the amphipathic helix at its C terminus to become attached to the membrane. Conversely, when FtsA is in the cytoplasm, the C terminus is not engaged in the attachment to the membrane, and it obstructs polymerization. ATP-dependent polymerization of FtsA inside membrane vesicles causes vesicle shrinkage, suggesting that, besides providing a membrane attachment for FtsZ, the FtsA C terminus may also introduce local alterations in the membrane to facilitate septation. IMPORTANCE FtsA is a protein needed in many bacteria to construct a septum that divides one fully grown cell, producing two daughters. We show that the region located at the C-terminal end of the Streptococcus pneumoniae FtsA protein works as a switch triggered by ATP, a molecule that stores energy. This region contains an amphipathic helix that obstructs the assembly of FtsA into polymers in the cytoplasm. In the presence of ATP, the obstruction is removed by switching the position of the helix. The switch directs the helix to the membrane and simultaneously facilitates the polymerization of the protein. The accumulation of FtsA molecules at the membrane causes distortions, an effect produced also by proteins such as MinD, MreB, and SepF that also contain amphipathic helixes as membrane attachment devices. In the case of FtsA, these distortions may also facilitate the initial events that lead to the division of bacteria.